Ocular Vascular Occlusive Disorders - Hayreh, Sohan Singh (Springer International Publishing : Imprint: Springer, 2015)
This book provides a comprehensive account of the pathogenesis, clinical features, and management of ocular vascular occlusive disorders, with the focus very much on the scientific evidence. This offers a sound basis for addressing the many controversies that surround these disorders, which collectively constitute the most common cause of visual impairment or blindness. The book is divided into two sections, the first of which addresses the basic science and encompasses vascular anatomy, blood supply and flow, and retinal tolerance time to acute ischemia. The second, clinical, section covers the presentation, clinical features, diagnosis, and treatment of the full range of vascular occlusive disorders of the retina, the choroid, the anterior segment of the eye, ophthalmic manifestations of carotid artery disease and the optic nerve.   In writing Ocular Vascular Occlusive Disorders, the author has drawn upon more than 55 years of experience in basic and clinical research. The book will be an invaluable source of information for general ophthalmologists, and particularly for retina specialists, neuro-ophthalmologists, and researchers. It is hoped that it will go far in rectifying the lack of in-depth scientific understanding that is the source of many misapprehensions and debates.